Analisis Hubungan Pengetahuan Pedagang dengan Kepatuhan Penerapan Hygiene Sanitasi Makanan di Kawasan Pasar Baruga: Studi Cross-Sectional - Siti Rabbani Karimuna; Rita Yusliani; Wa Ode Asrani; Rahma Triana; Nur Insan Sani (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2026)
Food hygiene and sanitation compliance among food traders in traditional markets is essential to prevent food contamination and foodborne diseases. Food traders have their own important role in maintaining quality and food safety through the application of good food hygiene and sanitation principles. However, the low level of trader knowledge regarding food hygiene and sanitation remains a factor that influences compliance with the application of food hygiene in traditional market environments. The relationship between trader knowledge and compliance with the application of food hygiene and sanitation in the Baruga Market area is the focus of this study. The approach used is an analytical observational approach with a cross-sectional design. A total of 15 food traders were included using total sampling by integrating the total sampling technique. Data collection was carried out through direct interviews using questionnaires, then the collected data were analyzed using univariate and bivariate analysis, then tested for significance using the association was tested using Fisher’s Exact Test due to the small sample size. The research findings show that the knowledge category is quite dominant among respondents, namely 10 traders (66.67%), the poor category is 4 respondents (26.67%), and the good category is 1 respondent (6.67%). Meanwhile, the level of compliance of traders in the implementation of food hygiene and sanitation is mostly categorized as good with 13 respondents (86.67%) and categorized as poor with only 2 respondents (13.33%). The chi-square test indicates a significant relationship between trader knowledge and compliance with the implementation of food hygiene and sanitation in the Baruga Market Area, as shown by a p-value of 0,022 (<0,05). In this regard, it is necessary to increase education and guidance for traders so that the implementation of food hygiene and sanitation can be carried out optimally to maintain food safety and consumer health